CSR and green accounting on financial performance: Good corporate governance as moderating variable - Melania Yovika Sunarjo; Catur Ragil Sutrisno; Annisa’ Kurnia (Kompartemen: Jurnal Ilmiah Akuntansi)
The purpose of this study  is to investigate how GCG influences the way that CSR and the use of Green Accounting affect the financial performance of mining sector businesses that are listed on the Indonesian Stock Exchange in 2020-2022 period. Based on the documentation method, a data collection technique that involves gathering yearly reports and sustainability reports about 150 samples from 50 mining sector enterprises that satisfied the research criteria were acquired. Purposive sampling is a data analysis technique used in this study. Using the IBM SPSS software, Moderated Regression Analysis (MRA) was the analysis method employed in this study. This study’s findings demonstrate that financial performance benefits from CSR and green accounting, and that GCG can increase these factor’s impact.